Hemipelvectomy for soft tissue sarcoma of the pelvis: a review of 13 cases - Sharifudin, Mohd Ariff; Wan Ismail, Wan Faisham Numan; Wan, Zulmi; Mat Zin, Nor Azman; Mohamed Amin, Mohamed Azril; Goh, Kian Liang (2014)
Introduction: Soft tissue sarcomas of the pelvis are rare and limited information is available in the literature. We evaluated patients with soft tissue sarcoma involving the pelvic bone who had internal and external hemipelvectomy in our institution to understand the anatomic extension of these tumours as well as the outcomes of surgical treatment. Methodology: Thirteen patients surgically treated for soft tissue sarcomas involving the pelvis between 2001 and 2010 were reviewed. Clinical and radiological data of patients who had an internal or external hemipelvectomy at any point in their clinical course were collected. Functional outcomes were evaluated using the Enneking’s criteria as adopted by the Musculoskeletal Tumor Society (MSTS). MSTS scores were obtained on the most recent follow up at various times after surgery. Functional outcome of patients with follow up period of less than four month were not evaluated. Oncologic outcomes include local recurrence, distant metastases and disease specific death were analyzed. Results: There were seven female and nine male patients, with mean age of 34.9 (range 14 to 65 years old). One patient underwent hemipelvectomy for recurrent soft tissue sarcoma. Majority (nine patients) of cases involved the ilium. The tumours were confined to the pelvis in eleven patients, with the other two patients had extension to the lumbar spine or the femur. Nine patients underwent limb-salvage procedures; six with curative intention and three for palliation only. External hemipelvectomy were performed on four patients, with one patient intended for palliation. Two patients from the limb-salvage group required bony reconstruction; one patient had hip transposition after resection involving the acetabulum, and another patient required non-vascularized autologous fibular strut graft following resection of the ilium and sacrum. Pedicled flap was required in three patients following amputation and one patient after limb-salvage procedure for reconstruction of soft tissue defects. Free oncologic margins were achieved in three patients from the amputation group and only two from the limb-salvage group. The average follow-up was 27 months (range 1 to 110 months). Nine patients were still alive on their last follow-up. Five of them survived with presence of the disease and four patients being disease free. Five patients (one amputee, four limb-salvaged patients) were complicated with infections. All patients had poor functional outcome on their recent follow up. Conclusion: The commonest extension in the bony pelvis was the iliium. Surgical resection had a high rate of morbidity and complications, with poor functional outcomes in both amputation and limb-salvage group.